Microalgae for Aquaculture - Arnaud Muller-Feuga (Blackwell Publishing, 2025)
Microalgae play a vital role in the rearing of aquatic animals like mollusks, shrimp, and fish, and are of strategic interest for aquaculture. This work reviews production systems of microalgae for aquaculture (e.g. Benemann, 1992; Muller-Feuga, 2000), partially reproduced and updated here (with kind permission from Kluwer Academic Publishers). All the fisheries and aquaculture production statistics quoted were obtained from the United Nations Food and Agriculture Organization (FAO, 2000). Wild phytoplankton is at the base of the entire aquatic food chain, supporting the production of renewable resources by some 100 106 t of fish per year. Overall annual ocean primary production is set at 1011 tDW (Longhurst et al., 1995; Pauly & Christensen, 1995). Microalgae’s main applications for aquaculture are related to nutrition, being used fresh – as a sole component or as a food additive to basic nutrients – for coloring the flesh of salmonids and for other biological activities. This report deals principally with the nutritional role of microalgae in aquaculture.